CRIMINAL SANCTIONS AGAINST CHILD OFFENDERS REPEAT OFFENSE - Moh. Haizul Ma’aly; Rahmatul Hidayati; Budi Parmono (International Journal of Cultural and Social Science, 2025)
This research focuses on the ambiguity of legal norms related to recidivism in the juvenile justice system in Indonesia, particularly within the framework of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). This research uses a normative juridical approach with conceptual analysis methods and a statute approach, supported by empirical data from five case studies of recidivist juvenile cases tried at the District Court "X" during the period 2022–2024. The research findings indicate that the absence of explicit norms regarding juvenile recidivism leads to disparities in sentencing, weak legal certainty, and potential violations of the principle of child protection. This research recommends the need to reformulate the SPPA Law to include substantive provisions regarding recidivism, as well as harmonization with the National Draft Criminal Code which has systematically included the definition of recidivism. The implications of this research emphasize the importance of a more responsive and consistent legal reform in ensuring justice for children in conflict with the law